2019
DOI: 10.1121/1.5126857
|View full text |Cite
|
Sign up to set email alerts
|

Use of magnetic resonance image registration to estimate displacement in the human earcanal due to the insertion of in-ear devices

Abstract: In-ear devices are used in a wide range of applications for which the device's usability and/or efficiency is strongly related to comfort aspects that are influenced by the mechanical interaction between the device and the walls of the earcanal. Although the displacement of the earcanal walls due to the insertion of the device is an important characteristic of this interaction, existing studies on this subject are very limited. This paper proposes a method to estimate this displacement in vivo using a registra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…We idealize our model here into a skin layer with thickness, s and a bony/cartilaginous/fatty part backing the skin with thickness B. Experiments showed that RD-foam earplugs induce insignificant earcanal deformation corresponding to a mean displacement <0.4 mm [38]. The surrounding tissue is therefore considered as elastic homogeneous materials with equivalent elastic properties much harder than skin or earplug (indicated as a hard substrate on Figure 2b).…”
Section: Finite Element Modeling Of a Rd-earplug Inside A Cylindrical...mentioning
confidence: 99%
See 2 more Smart Citations
“…We idealize our model here into a skin layer with thickness, s and a bony/cartilaginous/fatty part backing the skin with thickness B. Experiments showed that RD-foam earplugs induce insignificant earcanal deformation corresponding to a mean displacement <0.4 mm [38]. The surrounding tissue is therefore considered as elastic homogeneous materials with equivalent elastic properties much harder than skin or earplug (indicated as a hard substrate on Figure 2b).…”
Section: Finite Element Modeling Of a Rd-earplug Inside A Cylindrical...mentioning
confidence: 99%
“…In this section, we present FE simulations that account for actual curvatures of earcanal. To do so, we obtained a full 3D geometric model constructed from high-resolution MRI images based of a healthy human subject (a volunteer male participant of 29 year of age [38,51]) without any known hearing impairment or earcanal abnormalities. Figure 1a shows the CAD model constructed from those MRI images.…”
Section: Pressure In a More Realistic Axisymmetric Earcanalmentioning
confidence: 99%
See 1 more Smart Citation
“…At the Fitting/positioning phase (F), questionnaires or observations are commonly used. At the Interaction phase (I), the use of field attenuation estimation systems [90] (FAES), microphones or medical images (e.g., from magnetic resonance imaging MRI scanners [91]) is possible. Visual inspections could also be used for assessing the fit quality, but this is a much less robust method [65].…”
Section: Comfort Model Evaluation Instrumentsmentioning
confidence: 99%
“…The latter requires the knowledge of the EC shape function between the eardrum and the coupling duct and the geometric dimensions (inner radius and length) of the coupling duct. The EC shape can be obtained from CT or MRI images [27], 3D scans [28], EC imprint [26] or estimated using indirect acoustic method [29]. In theory, the EA model also requires the tympanic membrane acoustic impedance.…”
Section: Experimental Setup and Measurement Proceduresmentioning
confidence: 99%